Family support and prayer are invaluable coping strategies for our recovery: Experiences of persons living with cardiovascular diseases - Ivy Selorm Tsedze; Frank Edwin; Bennett Owusu; Victor Kwasi Dumahasi; Nkosi Nkosi Botha; Nancy Innocentia Ebu Enyan (PLoS ONE, 2025)
Background It is estimated that 61% of deaths caused by Cardiovascular Diseases (CVDs) globally are attributed to lifestyle-related risk factors including tobacco use, alcohol abuse, poor diet, and inadequate physical activity. Meanwhile, inadequate knowledge and misperceptions about CVDs are disproportionately increasing the prevalence of CVDs in Africa. Moreover, pre-diagnosis awareness/knowledge about CVDs among patients is essential in shaping the extent and scope of education to be provided by healthcare workers. Objective Explore the experiences of patients living with CVDs (PLwCVDs) and accessing care at the Cardiothoracic Centre, Ho Teaching Hospital, regarding their knowledge of CVD-risk factors and coping strategies that work for them. Method We leveraged descriptive phenomenological design to explore the experiences of patients accessing care at the Cardiothoracic Centre at the Ho Teaching Hospital, Ghana. Using the purposive sampling technique, 17 PLwCVDs for 3yrs and above were recruited and included in the study. Thematic analysis was conducted using the qualitative computerised data software, NVivo version 14. Recruitment of participants and general conduct of the study commenced on November 1, 2023 and ended on April 30, 2024. Findings We found that PLwCVDs and accessing care at the Cardiothoracic Centre at Ho Teaching Hospital have adequate pre-diagnosis awareness about CVD-risk factors and their knowledge of same was optimal. Moreover, past unhealthy lifestyles (such as poor dieting, abuse of alcohol, smoking, and inadequate physical activity) may have contributed to participants developing the CVDs. Furthermore, prayers and participation in church activities were the main coping strategies employed by the participants in dealing with CVDs. Conclusion The PLwCVDs and receiving treatment at the Cardiothoracic Centre at the Ho Teaching Hospital are knowledgeable in the CVD-risk factors and adopting positive coping strategies. The Cardiothoracic Centre and government must explore social media facilities to intensify public education and also correct misconceptions about CVDs.